(untitled) (Hematology Meeting Reports, 2009)
Certain growth factors exist in relatively high concentrations in fluids swallowed by the fetus and neonate; namely amniotic fluid, colostrum, and human milk. We postulated that; 1) after these factors are swallowed they are not enterally digested into non-functional units, but remain biologically active, 2) the ingested factors bind to specific receptors on the luminal surface of villous enterocytes where they exert a topical antiapoptotic effect, 3) the ingested factors are not absorbed into the blood and have no systemic effect, 4) when a fetus is delivered prematurely and amniotic fluid swallowing abruptly ceases, if the patient is NPO (thus receiving no growth factors from colostrum or milk) disuse atrophy of the small bowel mucosa can begin, leading to feeing intolerance once milk feedings are started. We developed a sterile, isotonic, growth factor-containing solution, simulating second trimester amniotic fluid. We called the fluid SAFEstart® (an acronym for Simulated, Amniotic Fluid for Enteral administration); a patent was obtained by the University of Florida. The growth factors contained in SAFEstart were concentrated 10 fold above natural amniotic fluid, so that 20 mL/k/d of SAFEstart would provide the amount of growth factors ingested by a fetus swallowing 200 mL/k/d of amniotic fluid. Preclinical studies on stability and digestion were followed by six clinical trials. Whether mixed with human milk, preterm infant formulas, or kept by itself, SAFEstart was stable for at least three weeks frozen, with only minimal and gradual degradation of activity in the weeks thereafter. No evidence of absorption of factors into the blood and no systemic effects were observed after usage. Four clinical trials have examined its use to prevent feeding intolerance and two additional trials have examined its treatment use among neonates with established feeding intolerance. CONCLUSIONS: One hundred-twenty neonates have now participated in six SAFEstart trials. It is feasible to administer 20 mL/k/d of SAFEstart (2.5 mL/k every 3 h) to ill preterm neonates, and it is well tolerated, with no safety issues uncovered to date. Early controlled studies suggest efficacy in preventing feeding intolerance and also in treating established feeding intolerance, presumably by topical actions of relevant growth factors on the small bowel mucosa. Multicentered randomized, placebo controlled trials are now needed to estimate the risks and benefits of administering SAFEstart to neonates who are otherwise NPO.